Biophotonics: Bio‐Inspired Band‐Gap Tunable Elastic Optical Multilayer Fibers (Adv. Mater. 15/2013). (12th April 2013) - Kolle, Mathias; Lethbridge, Alfred; Kreysing, Moritz; Baumberg, Jeremy J.; Aizenberg, Joanna; Vukusic, Peter
<x xml:space="preserve">Abstract</x> The back cover illustrates band‐gap tunable bioinspired photonic fibers created by Peter Vukusic, Mathias Kolle, and co‐workers on page 2239 that incorporate the structural key elements responsible for a tropical fruit's bright coloration. In the foreground a rendering of a gradually strained, colorchanging fiber is winding around another real fiber. The background features the cells in the fruit's skin. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>